A new spittlebug species of Deois (Pandysia) (Hemiptera, Cercopidae, Ischnorhininae) with a key to species of the subgenus - Paladini,Andressa (2016)
ABSTRACT Deois (Pandysia) paschoali sp. nov. from southern Brazil is described and illustrated. This species can be distinguished from other congeners by the following characters: aedeagus with dorsal margin serrate and paramere with a truncate and serrate spine. A key to species of Pandysia is provided.